Can patients be selected for transcatheter edge‐to‐edge repair based on the baseline transmitral gradient?. Issue 4 (11th March 2023) - Ueyama, Hiroki; Block, Peter C.
Key Points: Baseline transmitral gradient can predict reduction in left atrial pressure and residual transmitral gradient after transcatheter edge‐to‐edge repair (TEER). Understanding the possible multiple causes of elevated transmitral gradient before and after TEER may be important for selecting patients. Further research is necessary to elucidate the complex interaction of mitral regurgitation, the mitral annulus, left atrial, and ventricular function and their response to TEER.